Research on weld formation mechanism of laser-MIG arc hybrid welding with butt gap. (January 2021) - Huang, Hanxuan; Zhang, Peilei; Yan, Hua; Liu, Zhengjun; Yu, Zhishui; Wu, Di; Shi, Haichuan; Tian, Yingtao
Highlights: The variable butt gap is used to study the gap bridging ability of laser-MIG arc hybrid welding. Developed the welding process of laser-MIG arc hybrid welding under larger butt gap. Laser-arc distance affects weld formation by affecting arc parameters and droplet transition. Droplet transition is a mixture of short circuit transition and liquid bridge transition. Abstract: At present, there are few researches on laser -MIG arc hybrid welding with a large butt gap. In this paper, laser-MIG arc hybrid welding is used to weld low-alloy high-strength steel with a thickness of 3 mm, and a laser-MIG arc hybrid welding process under large gap conditions is developed. This paper studies the effects of arc voltage, laser-wire distance, and wire feed speed on the gap bridging capability of hybrid welding under different butting gaps. Under the condition of the 1 mm butt gap, the influence mechanism of laser-wire distance on weld the weld formation of hybrid welding is analyzed by combining high-speed photography, welding current and voltage waveform, the macroscopic and microscopic morphology of the weld. The results show that there are optimal process parameter values for the effects of arc voltage and laser-wire distance on the gap bridging capability of hybrid welding. Adjusting the laser-wire distance can optimize the energy distribution of laser on the welding wire and weld pool, thus controlling the arc current, voltage, and droplet transition mode, and finally affecting the weld penetration and forming. When the laser-wire distance is 0 mm, the droplet transition frequency is the fastest, and the droplet transition is a mixture of short circuit transition and liquid bridge transition. At this point, the welding rate is the fastest and the welding process is the most stable. However, by comprehensively integrating factors such as the gap bridging capability and the weld penetration, the optimal processing parameters are obtained when the laser-wire distance is 0.5 mm.